Transient micro-elastography: a novel non-invasive approach to measure liver stiffness in mice - Bastard, Cècile; Bosisio, Matteo R.; Chabert, Michèle; Kalopissis, Athina D.; Mahrouf-Yorgov, Meriem; Gilgenkrantz, Hélène; Mueller, Sebastian; Sandrin, Laurent (World journal of gastroenterology, 2011)
METHODS: A novel transient micro-elastography (TME) device, dedicated to LS measurements in mice with a range of measurement from 1-170 kPa, was developed using an optimized vibration frequency of 300 Hz and a 2 mm piston. The novel probe was validated in a classical fibrosis model (CCl4) and in a transgenic murine model of systemic amyloidosis. - RESULTS: TME could be successfully performed in control mice below the xiphoid cartilage, with a mean LS of 4.4 ± 1.3 kPa, a mean success rate of 88%, and an excellent intra-observer agreement (0.98). Treatment with CCl4 over seven weeks drastically increased LS as compared to controls (18.2 ± 3.7 kPa vs 3.6 ± 1.2 kPa). Moreover, fibrosis stage was highly correlated with LS (Spearman coefficient = 0.88, P < 0.01). In the amyloidosis model, much higher LS values were obtained, reaching maximum values of > 150 kPa. LS significantly correlated with the amyloidosis index (0.93, P < 0.0001) and the plasma concentration of mutant hapoA-Ⅱ (0.62, P < 0.005). - CONCLUSION: Here, we have established the first non-invasive approach to measure LS in mice, and have successfully validated it in two murine models of high LS.